Cosmopolitan Palembang: Palembang's Interconnection and Global Trade in 1900-1930 - Farida Ratu Wargadalem; Diki Tri Apriansyah Putra; Wasino Wasino (History Department, Semarang State University and Historian Society of Indonesia, 2023)
The interconnection and global trade developing interrelated regional linkages is an important phenomenon for modern developments, interestingly emphasizing historical context. This aligns with the historical context of Palembang, a region with long-establishing international relations and is considered a cosmopolitan city with global-scale connections toward the 20th century. Therefore, this study aimed to evaluate Palembang's interconnection and global trade from 1900-1930, mainly emphasizing the exploration of worldwide networks and the transformation of the region as a cosmopolitan city. The analysis used a historical method with four stages: heuristics, verification, interpretation, and historiography. The results showed that Palembang experienced rapid progress after its export commodities, such as coffee, rubber, wood, tea, oil, coal, etc., were extensively traded in the world market. European investors and multinational companies, including Handelsvereeniging Amsterdam, Cultuurmaatschappij Indragiri, Straits Sunda Syndicate, etc., were also competing to open and expand their business in the city. This economic progress triggered the transformation of Palembang into a cosmopolitan city, promoting the impact of social change in the environment. Interkoneksi dan perdagangan global yang menimbulkan keterkaitan wilayah satu sama lain menjadi fenomena penting bagi perkembangan dunia saat ini. Tentu sangat menarik apabila interkoneksi dan perdagangan global dilihat dari konteks kesejarahan. Salah satu wilayah yang telah lama menjalin hubungan internasional adalah Palembang. Menjelang abad 20, Palembang hadir sebagai kota kosmopolitan dengan koneksi berskala global. Artikel ini membahas tentang interkoneksi dan perdagangan global Palembang tahun 1900-1930. Fokus utamanya adalah menelusuri jaringan perdagangan global serta transformasi Palembang sebagai kota kosmopolitan. Artikel ini bertujuan untuk menjelaskan jaringan perdagangan global dan transformasi kota kosmopolitan di Palembang. Metode yang digunakan adalah sejarah dengan empat tahapan: heuristik, verifikasi, interpretasi, dan historiografi. Hasil penelitian menunjukkan bahwa Palembang telah mengalami kemajuan pesat sejak komoditas ekspornya seperti kopi, karet, kayu, teh, minyak, batubara, dan lain-lain sangat laku di pasar dunia. Investor Eropa, dan perusahaan multinasional seperti Handelsvereeniging Amsterdam, Cultuurmaatschappij Indragiri, Straits Sunda Syndicate, dan lain-lain berlomba-lomba membuka, dan memperluas lahan bisnisnya di daerah ini. Kemajuan ekonomi ini memicu transformasi Palembang menjadi kota kosmopolitan. Serta membawa dampak perubahan sosial dalam masyarakat Palembang.